Dermatan Sulfate and LMW Heparin Enhance the Anticoagulant Action of Activated Protein C - Fernández, José A.; Petäjä, Jari; Griffin, John H. (Thrombosis and Haemostasis, 1999)
Unfractionated heparin potentiates the anticoagulant action of activated protein C (APC) through several mechanisms, including the recently described enhancement of proteolytic inactivation of factor V. Possible anticoagulant synergism between APC and physiologic glycosaminoglycans, pharmacologic low molecular weight heparins (LMWHs), and other heparin derivatives was studied. Dermatan sulfate showed potent APC-enhancing effect. Commercial LMWHs showed differing abilities to promote APC activity, and the molecular weight of LMWHs correlated with enhancement of APC activity. Degree of sulfation of the glycosaminoglycans influenced APC enhancement. However, because dextran sulfates did not potentiate APC action, the presence of sulfate groups per se on a polysaccharide is not sufficient for APC enhancement. As previously for unfractionated heparin, APC anticoagulant activity was enhanced by glycosaminoglycans when factor V but not factor Va was the substrate. Thus, dermatan sulfate and LMWHs exhibit APC enhancing activity in vitro that could be of physiologic and pharmacologic significance.
Keywords: Dermatan sulfate; heparin; activated protein C; factor V